Pelatihan Rancang Bangun Smart home Berbasis IoT Untuk Siswa SMAIT Al Auliya Balikpapan - Yanti, Nur; Rachman, Fathur Zaini; Lesmideyarti, Dwi; Ihsan, Ihsan; Prasetyo, Mikail Eko; Sulistyo, Totok; Dahlan, Basri (Universitas Negeri Gorontalo, 2025)
Students now frequently use smartphones to access the Internet, demonstrating their proficiency with technology. Students who collaborate in groups to develop innovative goods and Internet of Things (IoT)-based smart home systems benefit from the project-based learning method in the classroom. Students are trained and mentored to create new works, such as scientific publications in the form of scholarly articles and prototypes with remote control of electrical gadgets in residential houses over the internet. For students with a vocational education background, such as those attending Vocational High Schools (SMK), technology-based instruction is typically pertinent. However, SMAIT Al Auliya Balikpapan students who have a general education background and are used to science instruction like the National Science Olympiad (OSN) received IoT information technology training in this community service project. As a result, the training offered to SMAIT Al Auliya Balikpapan students is unique and highly engaging. Using the waterfall technique through phases of problem-solving and communication with partners, creating learning guide modules as instructional resources, putting training and student mentoring into practice, and evaluating. One of the outcomes is a house prototype with a smart home system that allows users to remotely manage doors, fans, and lights via an Android smartphone with an internet connection. With real-time smartphone monitoring of the room temperature, humidity, door access, and the on/off status of household electronics, the student-designed system improves home security. It is advised that Android devices be always connected to a reliable internet network in order to preserve the monitoring system's continuity and guarantee that it operates in real-time without any delays. Additionally, as a result of the creative product design and development, students have authored a scientific study on the subject of Android-based smart homes that will be published. Students should have access to trainings or extracurricular activities pertaining to emerging technologies in an attempt to enhance their knowledge, abilities, mastery, and technological updating.